Hospital-Based and Freestanding Skilled Nursing Facilities: Any Cause for Differential Medicare Payments? - Korbin Liu; Kirsten J. Black (SAGE Publishing, 2003)
Differential Medicare payments for hospital-based and freestanding skilled nursing facilities (SNFs) were eliminated by the SNF prospective payment system initiated in 1998. Closures and high negative margins of hospital-based facilities have prompted consideration of the need to revisit payment adjustments for this group of SNFs. We examine case mix-related and other factors behind the cost differences between hospital-based and freestanding SNFs. Some payment adjustment, notably for nontherapy ancillary services, may be reasonable for the short term.